Multicultural Education Perspective Islamic Philosophy Of Education - Firmansah Kobandaha; Rakhmawati Rakhmawati; Muh. Rusli; Annisa Nuraisyah Annas (PT. Banjarese Pacific Indonesia, 2026)
This article discusses the concept of multicultural education from the perspective of Islamic educational philosophy. The diversity that exists in this country can lead to conflict due to differences in ethnicity, culture, religion, and so on, if not based on tolerance for each other. Multicultural education is an educational process that develops the full potential of humans who have different cultures, nationalities, and religions. The concept of multicultural education is expected to minimize conflicts that arise from differences in perspectives, attitudes, culture, and so on in society. In Islam, Islamic educational philosophy is a science that studies various issues related to education, such as humans as subjects and objects of education, curriculum, methods, environment, teachers, and so on based on Islamic teachings sourced from the Qur'an and al-Hadith. The Qur'an discusses the concept of multicultural education a lot, such as the concept of mutual recognition and respect for various cultures, races and religions, including Surah Al Hujurat verse 13 and Surah Ar Rum verse 22.